Research progress of T cells in cholangiocarcinoma - Wang, Zhiming; Dai, Yunyan; Zhou, Yunpeng; Wang, Yi; Chen, Pinggui; Li, Yaoxuan; Zhang, Yunfei; Wang, Xiaocui; Hu, Ying; Li, Haonan; Li, Gaopeng; Jing, Yukai (Frontiers in Immunology, 2025)
Cholangiocarcinoma (CCA), a malignant tumor, is typically challenging to detect early and often results in a poor prognosis. In recent years, research interest has grown in the potential application of immunotherapy for CCA treatment. T cells, as a crucial component of the immune system, play a significant role in immune surveillance and therapy for cholangiocarcinoma. This article provides a review of the research advancements concerning T cells in cholangiocarcinoma patients, including their distribution, functional status, and correlation with patient prognosis within the tumor microenvironment. It further discusses the potential applications and challenges of immunotherapy strategies targeting T cells in CCA treatment and anticipates future research directions. A more profound understanding of T cells’ role in cholangiocarcinoma can guide the development of clinical treatment strategies, thereby enhancing patient survival rates and quality of life. Finally, we explored the potential risks and side effects of immunotherapy for T-cell cholangiocarcinoma.